2022
DOI: 10.1093/occmed/kqac050
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial work environment among educators during the COVID-19 pandemic

Abstract: Background The education sector has been heavily impacted by COVID-19. While the impact on school-aged children has received much attention, less attention has focused on the experiences of educators. Aims To compare various dimensions of the psychosocial work environment and health outcomes between educators engaged in online learning to those engaged in in-person learning in the Canadian province of Ontario. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…al., 2022). This is supported by Smith et. al (2022) that stated in their research that among education workers, those who engaged in online education have worse psychosocial exposures, leading to high rates of burnout.…”
Section: Statement Of Problemsupporting
confidence: 70%
“…al., 2022). This is supported by Smith et. al (2022) that stated in their research that among education workers, those who engaged in online education have worse psychosocial exposures, leading to high rates of burnout.…”
Section: Statement Of Problemsupporting
confidence: 70%
“…The outbreak of the coronavirus disease (COVID-19) has affected countries around the world, posing enormous challenges. The strain on healthcare systems and the education sector due to the COVID-19 pandemic has led to increased psychological distress and burnout among healthcare workers and teachers ( 1 , 2 ). There is no doubt that employees of these occupational groups are working in the most adverse environment regarding psychosocial work conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have demonstrated that the COVID-19 pandemic has caused psychological distress, anxiety, depression, and, in some cases, death by suicide among healthcare workers (3)(4)(5) also the sudden change in the educational system pressured schools to formulate a teaching-learning program that will meet the requirement of the new normal classroom setting. Teachers with online learning reported some problems such as higher role conflicts and less support from supervisors and co-workers, distress, and anxiety (2,6).…”
Section: Introductionmentioning
confidence: 99%